(Study on effect of Delignification and Fermentation of Clove Stem on the Yield and its Oil Quality) - Agus Sudibyo; Juli Astuti (Warta Industri Hasil Pertanian, 2008)
The aim of this study was to determine the effect of clove stem preparation (delignification and fermentation) on the yield and quality of clove stem oil. The clove stem (Syzigium aromaticum, L) were obtained from Institute for Research and Development of Medical Plants and Spice, Bogor meanwhile Trichoderma vired mold was taken form Center for Research and Development of Biology, Indonesia Institute of Scince (LIPI) Bogor. It was dried until maximum moisture content of 12 %. Expriment was conducted in ywo replications base on these treatments, i.e. delignification temperature (60'C, 80'C) and fermentation time (2,4,6 and 8 dayas). Sodium hydroxide solution (NaOH 0.5%)was used for delignification. The ditillation process was conducted at 100'-2'C during 6 hours and ambient pressure condition. The clove stem oil quality were analyzed for the yield, specific gravity at 25'C, rotary index and eugenol content. The results showed that increased of fermentation time was followed by decreased of the clove stem oil quality parameter. It was indicated that the best treatment in term of the yield and quality which about 5.62 % (w/w), specific gravity 1.074, rotary index 1.545 and eugenol content 95.4% was that treating clove stem with delignification at 60'C and fermentation time for 6 day. The clove stem oil produced using treatment of fermentation time were in the range of physico-chemical quality standardof clove oil given by SNI no 06-2387-1998